2022
DOI: 10.1016/j.jamda.2021.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining Postdiagnostic Care and Support in Young-Onset Dementia

Abstract: Although dementia has a profound impact in general, young-onset dementia causes additional problems and challenges as people are affected in their prime years. Awareness has increased that people with young-onset dementia and their families have specific care needs and dedicated services are necessary to accommodate those needs. However, in many countries, age-appropriate care and support for people with young-onset dementia is still largely unavailable. In this special article, barriers as well as facilitator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Similar challenges have been identified internationally, in Ireland recommendations for a young-onset dementia service included named key-workers and clear pathways of communication (Fox et al, 2020), while in Australia a “call to action” included recommendations focusing on service integration and re-conceptualising young-onset dementia within the health-system (Cations et al, 2021). In the Netherlands a successful model of care has been developed involving the establishment of a knowledge centre, working in partnership with the health-service, to provide staff education and increase tailored support (Bakker et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similar challenges have been identified internationally, in Ireland recommendations for a young-onset dementia service included named key-workers and clear pathways of communication (Fox et al, 2020), while in Australia a “call to action” included recommendations focusing on service integration and re-conceptualising young-onset dementia within the health-system (Cations et al, 2021). In the Netherlands a successful model of care has been developed involving the establishment of a knowledge centre, working in partnership with the health-service, to provide staff education and increase tailored support (Bakker et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Given that younger people with dementia are at a different stage of life compared to older people, age-appropriate services with available postdiagnostic support is essential for their ongoing management. Individuals with YOD and their families have unique needs that are not within the scope of aged care services and prefer a specialist YOD service [28,29]. Specialist YOD services provide a “one-stop-shop” for assessment which include medical (psychiatry, neurology, geriatrics), allied health/multidisciplinary approach (neuropsychology/cognition, occupational therapy/functional, speech therapy), and access to neuroimaging, lumbar punctures and cerebrospinal fluid (CSF) analysis [30] and other investigations [31].…”
Section: Service Provision and Post-diagnostic Supportmentioning
confidence: 99%
“…People living with YOD need to be supported by their local communities to remain living in their own neighbourhoods. [10][11][12] Rabanal et al emphasised the importance of unique services to meet the needs of people living with YOD, compared to those with lateonset dementia. 13 However, a literature review revealed a lack of information on YOD care, highlighting the need to deliver appropriate and timely service.…”
Section: Introductionmentioning
confidence: 99%
“…People living with YOD need to be supported by their local communities to remain living in their own neighbourhoods 10–12 . Rabanal et al .…”
Section: Introductionmentioning
confidence: 99%